Hydrolysis of chrome shavings; application of collagen hydrolysate and “acrylic-protein” in post tanning operations - Cantera, Carlos (1997)
The tanning industry is a generator of liquid wastes as well as tanned and non-tanned solid wastes plus those derived from the waste water treatment plant. This situation requires the introduction of “cleaner leather technologies” and of treatment systems for both effluents and solid wastes, so that pollutant discharge standards can be reached. Particularly, solid wastes from chrome tanned leather require special attention because of their volume and of the requirements by authorities for their direct disposal in landfill sites. A technological alternative for upgrading these wastes is the detanning of chrome shavings (and wet-blue trimmings) through alkaline hydrolysis assisted oy the action of proteolytic enzymes at a moderate temperature (55°C), so as to obtain a collagen hydrolysate and a “chrome cake”, both with potential applications in the tanning industry. This paper describes experiment performed in the application of collagen hydrolysates and of “acrylicprotein” polymers (acrylic acid / hydrolysed collagen polymers) in post-tanning processes for the manufacture of bovine leather for “softy” uppers. The retanning capacity of. synthesized polymers and the positive effects attained from hydrolysates in the fatliquoring process (“nutrient and cosmetic effects”) were assessed by means of a subjective evaluation and through a statistical analysis of the physico-mechanical strengths of the leathers. Results are also shown from a laboratory test with chrome tanned hide powder aimed at assessing the “retanning degree” of these products. The test was developed to allow the comparison of die reiamiing agents under analysis and to complement the retanning test.